COP17 Event - Climate Smart Agriculture: Opportunities and Challenges for African Farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
During COP17 in South Africa, Durban, the Research Progam on Climate Change, Agriculture and Food Security (CCAFS) organised, together with the Technical Centre for Agricultural and Rural Cooperation (CTA) and the Food, Agriculture and National Resources Policy Analysis Network (FANRPAN), an side event on opportunities and challenges for African farmers within climate-smart agriculture. The event took place at the Africa Pavilion, on 5 December 2011. Photo: C. Schubert (CCAFS).